The library in the «paper» and realized projects of Russian architects of the XIXth century (Prospects for the use of the biographical method of study) - K. B. Lavrova (Библиосфера)
The article analyzes the reasons of turning Russian architects of the XIXth - beginning of the XXth century to the design of library buildings. It is shown that library becomes the object of creativity of the architects of different styles and schools. The prospect of using the biographical method for studying the personalities of library architects is proved. The importance of studying the library architecture in paper and realized ones is reasoned.